Safety and efficacy of personal care products containing colloidal oatmeal - Criquet M; Roure R; Dayan L; Nollent V; Bertin C (Dove Medical Press, 2012)
Maryline Criquet,1 Romain Roure,1 Liliane Dayan,2 Virginie Nollent,1 Christiane Bertin11Johnson & Johnson Santé Beauté France, Issy les Moulineaux, 2Independent consultant dermatologist, Paris, FranceBackground: Colloidal oatmeal is a natural ingredient used in the formulation of a range of personal care products for relief of skin dryness and itchiness. It is also used as an adjunctive product in atopic dermatitis. The safety of personal care products used on vulnerable skin is of particular importance and the risk of developing further skin irritations and/or allergies should be minimized.Methods: In a series of studies, we tested the safety of personal care products containing oatmeal (creams, cleansers, lotions) by assessing their irritant/allergenic potential on repeat insult patch testing, in safety-in-use and ocular studies using subjects with nonsensitive and sensitive skin. We also tested the skin moisturizing and repair properties of an oatmeal-containing skin care product for dry skin.Results: We found that oatmeal-containing personal care products had very low irritant potential as well as a very low allergenic sensitization potential. Low-level reactions were documented in 1.0% of subjects during the induction phase of repeat insult patch testing; one of 2291 subjects developed a persistent but doubtful low-level reaction involving edema during the challenge phase in repeat insult patch testing. No allergies were reported by 80 subjects after patch testing after in-use application. Sustained skin moisturizing was documented in subjects with dry skin that lasted up to 2 weeks after product discontinuation.Conclusion: Our results demonstrate that colloidal oatmeal is a safe and effective ingredient in personal care products. No allergies were reported by consumers of 445,820 products sold during a 3-year period.Keywords: Avena sativa, colloids, protective agents, atopic dermatitis, irritant dermatitis, allergenic dermatitis, skin care